Knowledge, apptitude and practice: smoking and gutka habits in a lower socio-economic cohort - Khan, Aazmeer Mohammad; Kidwai, Saera Suhail; Akhtar, Saima; Ara, Jamal (International Journal of Research in Medical Sciences, 2018)
Background: Smoking and smokeless tobacco use is the major cause of death and disease in South Asia, the use of gutka has surpassed that of smoking in this region thus, acting as a major contributor to oral and esophageal cancer especially in the younger population. Authors have designed this study to explore the knowledge, apptitude and practice regarding smoking and gutka use in a lower socio-economic cohort and observe the impact of education, income and type of profession on the users. Methods: This cross sectional descriptive survey is conducted in Creek General Hospital, Korangi, Karachi. The study design is non-probability convenience. A questionnaire is used to quantify the frequency of smoking-related knowledge-attitude-practice, knowledge and attitude about tobacco-related disease and, smoking cessation-related thoughts and practice. Data is analysed in SPSS 16. Results: A total of 250 subjects participated in this descriptive study, 133 subjects (22% females and 62.6% males) were found addicted to smoking or smokeless tobacco product with stress, seeking pleasure and peer pressure being the most convincing factor to initiate their habit.90% of the users want to stop using the substance of abuse and 80 have at least once tried to quit the habit. Conclusions: This study shows a direct relationship between level of education and socioeconomic status with use of addictive substance. It also resulted in identifying the desire to quit in our cohort and need for formulating a plan specifically for the target population to focus not only to remove the cause, but also to empower them to take responsibility for their own well being.